Komunikasi Persuasif Melalui Video Bahaya Narkoba dan Rokok di SMK Negeri 5 Kecamatan Padang Ulak Tanding Kabupaten Rejang Lebong Provinsi Bengkulu - Vethy Octaviani; Sapta Sari (Journal of Community Development, 2024)
Tanjung Sanai Village, Padang Ulak Tanding District, Rejang Lebong Regency, Bengkulu Province. included in drug-prone areas based on research data from the Bengkulu Province National Narcotics Agency in the framework of the 2020 P4GN which mapped this drug-prone area with danger and alert categories and there are several cases where teenagers are trapped in the problem of smoking and use of illegal drugs. This is of course very concerning, so the team of lecturers and students from the Communication Studies Program, Faculty of Social Sciences, Dehasen Bengkulu University carried out Community Service (PKM) activities as a prevention effort, especially in drug and cigarette abuse among teenagers. The location chosen for this PKM activity was SMKN 5 Rejang Lebong which is located in Tanjung Sanai Village. The stages of this community service activity consist of the preparation stage, the activity implementation stage by providing materials, video screening, and the discussion stage. This is done by adopting a persuasive communication model by being equal, increasing discussions, directing gently, accompanying and listening to the complaints of activity participants so that the material can be well received. This activity went well, based on the results of the PKM team's observations, the persuasive communication approach used during the activity was able to provide good understanding to students in general, as seen from the students' enthusiasm during the discussion. It is hoped that this activity can be an anticipatory step in preventing the bad effects of drugs and cigarettes as well as a form of active concern for lecturers and students of the Communication Science Study Program, Faculty of Social Sciences, Dehasen Bengkulu University in transferring knowledge, skills and technology to the community, especially village youth.